Synthesis of stable monodisperse AuPd, AuPt, and PdPt bimetallic clusters encapsulated within LTA-zeolites - Otto, Trenton (2016)
AuPd, AuPt, and PdPt bimetallic clusters uniform in size and composition were prepared using hydrothermal assembly of LTA crystals around cationic precursors stabilized by protecting mercaptosilane ligands. The sulfur moiety in these bifunctional ligands forms adducts that prevent premature reduction or precipitation of metal precursors during crystallization. The silane groups can form bridges with silicate oligomers as they form, thus enforcing homogeneous distributions of precursors throughout crystals and ensuring that subsequent reductive treatments lead to the two elements residing within small and nearly monodisperse clusters. Their confinement within LTA crystals, evident from microscopy and titrations with large poisons, renders them stable against sintering during thermal treatments at high temperatures (820–870 K). Infrared spectra of chemisorbed CO show that bimetallic surfaces are free of synthetic debris after thermal treatments; these spectra also indicate that intracluster segregation occurs upon CO chemisorption, a demonstration of the presence of the two elements within the same clusters. The number and type of atoms coordinated to a given absorber atom, determined from the fine structure in X-ray absorption spectra, are consistent with bimetallic structures of uniform composition. The rates of ethanol oxidative dehydrogenation on these bimetallic clusters were essentially unaffected by exposure to dibenzothiophene, a large poison that suppresses rates on unconfined clusters, indicating that bimetallic clusters are protected within the confines of LTA crystals. These synthetic protocols seem generally applicable to other bimetallic compositions and zeolites, for which the monometallic counterparts have been successfully encapsulated within several microporous frameworks using ligand-stabilized precursors and hydrothermal crystallization methods.